The glutamate metabotropic receptor 5 (GRM5) gene is associated with beef cattle home range and movement tortuosity - Cristian A. Moreno García; Huitong Zhou; David Altimira; Robyn Dynes; Pablo Gregorini; Sadeepa Jayathunga; Thomas M. R. Maxwell; Jonathan Hickford (Journal of Animal Science and Biotechnology, 2022)
Abstract Background The grazing behaviour of herbivores and their grazing personalities might in part be determined genetically, but there are few studies in beef cattle illustrating this. In this study, we investigated for first time the genetic variation within a candidate ‘grazing gene’, the glutamate metabotropic receptor 5 gene (GRM5), and tested associations between variation in that gene and variation in grazing personality behaviours (GP-behaviours) displayed by free-ranging cows during winter grazing in the steep and rugged rangelands of New Zealand. Mature beef cows (n = 303, from 3 to 10 years of age) were tracked with global positioning system (GPS) and, with 5-minutes (min) relocation frequency, various GP-behaviours were calculated. These included horizontal and vertical distances travelled, mean elevation, elevation range, elevation gain, slope, home range and movement tortuosity, variously calculated using daily relocation trajectories with repeated measurements (i.e., 7 to 24 days (d)) and satellite-derived digital elevation models (DEM). The different GP-behaviours were fitted into mixed models to ascertain their associations with variant sequences and genotypes of GRM5. Results We discovered three GRM5 variants (A, B and C) and identified the six possible genotypes in the cattle studied. The mixed models revealed that A was significantly associated with elevation range, home range and movement tortuosity. Similarly, GRM5 genotypes were associated (P < 0.05) to home range and movement tortuosity, while trends suggesting association (P <  0.1) were also revealed for elevation range and horizontal distance travelled. Most GP-behaviour models were improved by correcting for cow age-class as a fixed factor. The analysis of GP-behaviours averaged per cow age-class suggests that grazing personality is fully established as beef cows reached 4 years of age. Home range and movement tortuosity were not only associated with GRM5 variation, but also negatively correlated with each other (r = − 0.27, P < 0.001). Conclusions There seems to be a genetically determined trade-off between home range and movement tortuosity that may be useful in beef cattle breeding programmes aiming to improve the grazing distribution and utilisation of steep and rugged rangelands.